RUMAH PANGGUNG DAN KEARIFAN LOKAL: PENGETAHUAN EKOLOGIS KOMUNITAS DAYAK DAN MELAYU KALIMANTAN BARAT DALAM MITIGASI BENCANA BANJIR - Gunawan Wibisono; Enika Herawati; Mutia Betania; Herlan Herlan; Syarifah Ema Rahmaniah (Jurnal Ilmiah Sosiologi Agama (JISA), 2026)
This study examines the role of traditional stilt houses as local wisdom derived from the ecological knowledge of the Dayak and Malay communities in West Kalimantan in flood disaster mitigation. Stilt houses are not merely cultural heritage but also an adaptive strategy that integrates ecological, social, and gender aspects to address the risk of annual flooding. Using a qualitative case study approach in a purposively selected flood-prone location, data were collected through field observations, semi-structured interviews, and document analysis. The results show that stilt houses are built at specific heights and materials based on inherited ecological experiences, providing physical protection, food storage, and a center for social coordination during floods. An early warning system based on natural signs, mutual cooperation practices, and traditional rituals support community preparedness and strengthen social solidarity. Gender analysis reveals the strategic role of women in food management, adaptive agriculture, and logistics coordination, which complement men's roles in social structures and decision-making. Furthermore, the integration of local knowledge with modern strategies, including the use of social media for mitigation information, strengthens the community's adaptive capacity. These findings confirm that successful flood mitigation is determined not only by infrastructure, but also by social participation, cultural practices, and the sustainable application of local ecological knowledge. This research makes an important contribution to the development of inclusive, sustainable disaster mitigation policies rooted in the local wisdom of Dayak and Malay communities.